The Other side of Nashville - Transfilm Productions; MGM/UA Home Video (Firm) (N[ew] Y[ork], NY : MGM/UA Home Video, 1984)
A fascinating inside look at Nashville, as seen through the eyes of the stars who've made it one of the great centers of the music world.
Mine was the first heart she broke -- The other side of Nashville -- The gambler -- The claw -- Oh lonesome me -- The devil went down to Georgia -- Y'all come -- They call me the breeze -- Get above your raisin's -- Round the clock lovin'-- What'd I say -- Two more bottles of wine -- Racin' in the streets -- Goodbye to a river -- Blue Flame Cafe -- Amazing grace -- Will the circle be unbroken -- Your cheatin' heart -- Hey good lookin' -- Jesus just left Chicago -- Blueberry hill -- Matchbox -- Blue suede shoes -- Honey don't -- I walk the line -- Folsom Prison blues -- To be alone with you -- One too many mornings -- Girl from the north country -- To beat the devil -- Always on my mind -- Whiskey river -- Shenandoah.
VHS format.
Narrator, Bob Johnston.
Bobby Bare, Johnny Cash, Charlie Daniels, Gail Davies, Terri Gibbs, Emmylou Harris; Kris Kristofferson; Charlie McCoy; Willie Nelson; Carl Perkins; Donny Qualls; Rattlesnake Annie; Kenny Rogers; Ricky Skaggs; Porter Wagoner; Hank Williams, Jr.; Owen Davis.
Keywords: Country music; Country music -- Tennessee -- Nashville